PERKEMBANGAN MASA BAYI - Zaskya Rahmadani; Intan Yulia Putri; Linda Yarni (ADIBA : JOURNAL OF EDUCATION, 2024)
The first timea baby communicates by crying, for example a baby crying with with a loud cry means it is because of a stomach ache or the baby want to breastfeed and at the age of 2 months the baby usually starts babbling like combining certain life letters with sounds like the word “ma-ma”. Social development during infancy is a condition of situation where the baby can respond well to the people around him. For example, stealing attention fromparents and peoplearound him. When they are still babies, children do not yet know what moral behavior is right or wrong towards their surroundings. The development ofa baby’s moral behavior can be seen when the baby is 9-12 months old, atthat time the baby has begun to understand. Thisresearch aims to analyze language development,socialization, morals during infancy, the menthodc used in this reseach is literature carried out using library literature, whether in the from of books,notes or other reference sources.